APPLICATION OF UPWARD CONTINUATION FILTER FOR GEOMAGNETIC DATA INTERPRETATION IN GONDANG, BOJONEGORO AREA - Mustika Bohal, Yolanda; M, Mariyanto; Utama, Widya (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2020)
There are several manifestations of hot springs and mud pools in Gondang area, Bojonegoro, East Java, there were. This can be an indication of certain geological conditions. The description of these conditions can be done by measuring the geomagnetic method. A total geomagnetic anomaly has been generated through some geomagnetic values recorded in the region, which has been corrected using IGRF correction and diurnal correction. These steps were done to reduce external influences on the real value of the data. This research will use several variations of values in the Upward Continuation filter and one of them will be chosen to proceed as a model. Upward Continuation Filter is a process of transforming potential field data from a flat plane towards the higher plane. The purpose of this study is to compare the results of contour maps on several variations of the Upward Continuation value, to obtain the results of the separation of residual and regional anomalies using the Upward Continuation method, and to determine the value of the susceptibility distribution of inversion modeling in the Gondang region, Bojonegoro. Based on the results of data processing, it is known that the upward continuation value used is 100mdatum with a magnetic intensity value in the regional anomaly of 106.5 nT to 509.0. While the value of the residual anomaly is -232.1 nT to 159.4 nT. The 3D model was made using this residual anomaly which shows the low susceptibility distribution value in the range of -0.0298 to -0.0135 SI around the manifestation area, whereas the high susceptibility value has a value range of 0.0114 to 0.0466 SI interpreted as rock intrusion. Rock intrusion occurs within the area around the manifestation of mud pools.